2021
DOI: 10.1016/j.sjbs.2021.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Variations in length of stay of inpatients with COVID-19: A nationwide test of the new model of care under vision 2030 in Saudi Arabia

Abstract: Objective The coronavirus disease 2019 (COVID-19) has impacted the Kingdom of Saudi Arabia (KSA) as it has other nations. However, length of stay (LOS), as a healthcare quality indicator, has not been examined across the healthcare regions in the KSA. Therefore, this study aimed to examine factors associated with LOS to better understand the Saudi Health System's performance in response to the COVID-19 pandemic in the newly suggested five Saudi regional business units (BUs). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…The explanation of our findings in regard to outcome is consistent with several studies that reported the association of mortality with comorbidities, especially the risk factors of HTN, obesity, DM2, renal disease, and cardiovascular disease. 8 , 16 , 17 , 28–33 This study is also consistent with national studies that reported the association of complications of COVID-19, with mortality rate, ICU admission, and LOS 8 , 16 , 17 and our data is consistent with international studies that found significantly higher risk of death in COVID-19 inpatients with pre-existing obesity and complications of sepsis and multi-organ failure. 34 , 35 Other studies have found risk factors that have an impact on the severity of COVID-19 including certain demographics such as being male or of advanced age along with comorbidities such as DM2, HTN, cardiac diseases, asthma, chronic obstructive pulmonary disease (COPD), tuberculosis, pneumonia, ARDS, renal disease, and hepatic disease, along with behaviors such as smoking.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The explanation of our findings in regard to outcome is consistent with several studies that reported the association of mortality with comorbidities, especially the risk factors of HTN, obesity, DM2, renal disease, and cardiovascular disease. 8 , 16 , 17 , 28–33 This study is also consistent with national studies that reported the association of complications of COVID-19, with mortality rate, ICU admission, and LOS 8 , 16 , 17 and our data is consistent with international studies that found significantly higher risk of death in COVID-19 inpatients with pre-existing obesity and complications of sepsis and multi-organ failure. 34 , 35 Other studies have found risk factors that have an impact on the severity of COVID-19 including certain demographics such as being male or of advanced age along with comorbidities such as DM2, HTN, cardiac diseases, asthma, chronic obstructive pulmonary disease (COPD), tuberculosis, pneumonia, ARDS, renal disease, and hepatic disease, along with behaviors such as smoking.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical course and outcome may be used as quality indicators during admission. 8 , 16 , 17 Aseer and Najran were almost identical, and had the highest prevalence among inpatients in rates of ICU admission, length of stay, and referrals to other facilities. The mortality rate had the highest prevalence in Najran followed in order by Aseer, Jazan, and Bisha.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…After adjusting for known demographic and disease severity characteristics that may have affected the LoS among patients with COVID-19 our study revealed a mean LoS for the total sample of just over 10 days which is shorter than that observed by most international studies, 7 , 9 , 13 but similar to a recent study of all regions in the KSA. 15 Linear regression analysis revealed a statistically significant association between region and LoS and compared to Bisha (reference) at just over seven days, Jazan had just over 10 days (34% longer), Najran had 15 days (62% longer) and Aseer had 13 days (40% longer) ( Tables 3 and 4 ).…”
Section: Discussionmentioning
confidence: 93%
“… 7–9 , 13 , 14 A study in the KSA of cases during a four-month period from mid-March to mid-July 2020 observed a mean LoS of 11.85 days with a range of 9.3–13.3 days depending on the region. 15 Several factors have been identified as having an association with LoS. Comorbidities have an impact on LoS, ICU admission, and mortality; for example, several international studies observed increased LoS in patients with uncontrolled DM2 14 , 16–18 although one study in Iran did not find DM2 by itself to be statistically significant in affecting LoS.…”
Section: Introductionmentioning
confidence: 99%